Hybridization in North Island tree weta : a thesis submitted in fulfilment of the requirement for the degree of Master of Science in Zoology, Massey University, March 2014 - Mckean, Natasha (Massey University, 2014)
Hybridization has important implications for species concepts, understanding the speciation process, as well as the issue of sister species coexistence and conservation. Tree weta (genus Hemideina) are an interesting natural system for studying hybridization, as some species have multiple chromosome races that can interbreed, and all are broadly parapatric with at least one other species in the wild, so there are many opportunities for natural hybridization to occur. It is not known in many cases whether species pairs are hybridizing in the wild, or whether introgression occurs. This study focused on the interactions between H. thoracica and its two neighbouring species; H. crassidens and H. trewicki. Surveys of one area of sympatry between H. thoracica and H. crassidens, and one between H. thoracica and H. trewicki, were conducted to see if the parent species and putative hybrids could be easily distinguished, and to find out the relative ratios of the parents and putative hybrid individuals. Weta from the parent populations were studied in areas where they are sympatric as well as allopatric to look for evidence of possible divergence and/or introgression in sympatry. These studies showed that where these species pairs are sympatric, parent forms were predominant, with few morphological intermediates, despite parent species existing in similar proportions. Hemideina thoracica and H. trewicki differed in sympatry regarding both size and possibly life history, with H. thoracica females being larger and both sexes maturing later than H. trewicki. Hemideina thoracica and H. crassidens showed possible evidence of introgression, but no evidence of divergence in sympatry. Karyotypes, a mitochondrial locus, and eight nuclear loci were examined for evidence of introgression between the species pairs in sympatry. All putative hybrids (morphological intermediates) from both species pairs were found to be genetic hybrids, with strong evidence of being F1 hybrids. No evidence was found for introgression of karyotypes or of mitochondrial haplotypes in either case. No evidence of introgression was found at nuclear loci for H. thoracica and H. trewicki. However, H. thoracica and H. crassidens showed some overlap at nuclear markers in sympatry, suggesting a low level of introgression. There was also a sex-bias in the production of F1 hybrids, with most having a H. crassidens mother. Hemideina thoracica appears to interact differently with its two neighbouring species; H. crassidens and H. trewicki. Hemideina thoracica and H. trewicki appear to be reproductively isolated, and are possibly exploiting different niches. Hemideina thoracica and H. crassidens by contrast, showed no evidence of divergence and are presumably dealing with strong interspecific competition, as well as introgression where they meet. These two species are unusual in maintaining a bimodal hybrid zone in the apparent absence of assortative mating. They also contrast with Haldane’s rule, as F1 males have some level of fertility, while females are likely infertile. A sex-bias in the production of F1 hybrids may be due to ‘sexual exclusion’, and so could possibly provide an explanation of how H. thoracica has managed to displace H. crassidens from much of its former range.
Keywords: Tree wetas; North Island; New Zealand; Wētā; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology